A RANDOMIZED STUDY TO COMPARE LDL-C-LOWERING EFFECTS OF INCLISIRAN WITH USUAL CARE VS USUAL CARE ALONE IN PATIENTS WITH RECENT HOSPITALIZATION FOR AN ACUTE CORONARY SYNDROME: RATIONALE AND DESIGN OF THE VICTORION-INCEPTION TRIAL - Jeffrey L. Anderson, MD; Ann Marie Navar, MD, PhD; Neeraja Balachander, MBBS, PhD, MS; Nihar R. Desai, MD, MPH; Kirk U. Knowlton, MD (Elsevier, 2023)
Therapeutic Area: CVD Prevention - Primary and Secondary Background: Patients are at high risk for a recurrent cardiovascular (CV) event in the first year following acute coronary syndrome (ACS). Low-density lipoprotein cholesterol (LDL-C) is a modifiable risk factor for recurrent CV events. Despite the availability of lipid-lowering therapies (LLT), many patients fail to achieve guideline-recommended LDL-C <70 mg/dL in the year post-ACS. Early LDL-C evaluation and LLT intensification after recent ACS may reduce recurrent CV event risk. In prior Phase 3 trials, inclisiran plus maximally tolerated statin therapy effectively reduced LDL-C in patients with established atherosclerotic cardiovascular disease (ASCVD). As patients with an ACS within 3 months of screening were excluded from these trials, the efficacy of inclisiran in these patients is unknown. The objective of this study is to assess the LDL-C-lowering effect of inclisiran added to usual care, vs usual care alone, in patients recently hospitalized (in-patient/out-patient) for an ACS and with LDL-C ≥70 mg/dL despite statin therapy. Methods: VICTORION-INCEPTION (NCT04873934) is a Phase 3b, randomized, parallel-group, open-label, multicenter, United States-based trial enrolling eligible patients to receive inclisiran plus usual care or usual care (Figure). Concomitant LLT and routine LDL-C assessment are at the discretion of the managing physician to mimic real-world clinical practice. The primary endpoints are percent change from baseline in LDL-C and the proportion of patients achieving LDL-C <70 mg/dL. Key secondary endpoints include absolute change from baseline in LDL-C, absolute and percentage change in LDL-C at each post-baseline visit, the proportion of patients reaching pre-specified LDL-C targets, absolute and percentage change in other plasma lipids, the intensity of background LLT, and safety and tolerability of inclisiran. Conclusions: VICTORION-INCEPTION, an ongoing trial planned to complete in early 2024, will assess the effectiveness of inclisiran plus usual care for the management of patients with elevated LDL-C post-ACS despite receiving statin therapy.